Theoretical and Experimental Studies on the Corrosion Inhibition Potentials of Two Tetrakis Pyrazole Derivatives for Mild Steel in 1.0 M HCl - Louadi,Y.E. (2017)
The inhibition performance and mechanism of N1,N1,N3,N3-tetrakis((3,5-dimethyL-1Hpyrazol- 1-yl)methyl)propane-1,3-diamine (BF2) and N1,N1,N2,N2-tetrakis((3,5-dimethyl- 1H-pyrazoL-1-yl)methyl) benzene-1,2-diamine (BF4) for the corrosion of mild steel in 1.0 M HCl were investigated using weight loss method and electrochemical measurements. The results show that both tetrakis pyrazole derivatives act as good inhibitors, and inhibition efficiency follows the order: BF4 > BF2. Two tetrakis pyrazole derivatives are mixed type inhibitors exhibiting predominantly cathodic behavior. The Nyquist plots showed that, after increasing inhibitors' concentrations, charge-transfer resistance increased and double-layer capacitance decreased, involving increased inhibition efficiency. The adsorption of both inhibitors on a steel surface obeyed Langmuir model, thus, the thermodynamic and kinetic parameters were calculated and discussed. Quantum chemical parameters are calculated using the Density Functional Theory method (DFT). Correlation between theoretical and experimental results is discussed.